Cost–benefit analysis of fodder production as a low emissions development strategy for the Kenyan dairy sector - Kashangaki, John; Ericksen, Polly J. (International Livestock Research Institute, 2018)
Livestock production is a promising agricultural sector to explore in view of achieving greenhouse gas (GHG) emissions reduction, given that it is the largest source of emissions from agriculture. The combination of economic importance and high emissions intensities makes the Kenyan livestock sector a good opportunity for investment in low emissions development strategies.